Hubungan Perilaku Merokok dan Beban Kerja dengan Kejadian Hipertensi di Poli Penyakit dalam Rumah Sakit Graha Husada Bandar Lampung - Ellsa Diana Agustina; Hardono Hardono; Hana Zumaedza Ulfa; Riska Hediya Putri (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Hypertension is difficult for sufferers to realize because it has no specific symptoms. Hypertension in the elderly is a problem that is often found in the elderly today. One of the life habits that contributes to hypertension includes smoking and work history as triggers for hypertension in the elderly. The aim of this study was to determine the relationship between smoking behavior and work history with the incidence of hypertension in the elderly at the Internal Medicine Clinic, Graha Husada Hospital, Bandar Lampung. This type of quantitative research uses an analytical survey research design and a cross-sectional approach. The research was carried out in October 2024 at Graha Husada Hospital in Bandar Lampung. The population in this study was elderly people who suffered from hypertension with a sample size of 64 respondents. The sampling technique in this research used purposive sampling. The instruments used were questionnaires, blood pressure monitors and stethoscopes to measure blood pressure. Data analysis used the chi square test. The results of this study show that there is a relationship between smoking behavior with a p-value <0.001 (<0.05) and work history with a p-value <0.001 (<0.05) on the incidence of hypertension in the elderly. It is hoped that hospitals can provide reading media to increase patient awareness by socializing smoking behavior and reducing heavy work or doing friendly or light work so as not to trigger an increase in blood pressure.